Borderline resectable pancreatic cancer. Challenges and controversies. (July 2018) - Sabater, Luis; Muñoz, Elena; Roselló, Susana; Dorcaratto, Dimitri; Garcés-Albir, Marina; Huerta, Marisol; Roda, Desamparados; Gómez-Mateo, María Carmen; Ferrández-Izquierdo, Antonio; Darder, Antonio; Cervantes, Andrés
Highlights: Neoadjuvant therapy can improve outcomes in borderline resectable pancreatic cancer (BRCP). Pancreatic protocols with specific imaging techniques are essential to identify BRPC. A multidisciplinary team and surgical expertise are essential for successfully treating BRPC. Further research and international cooperation for a consensus strategy is needed. Abstract: Pancreatic cancer is a dismal disease with an increasing incidence. Despite the majority of patients are not candidates for curative surgery, a subgroup of patients classified as borderline resectable pancreatic cancer can be selected in whom a sequential strategy of neoadjuvant therapy followed by surgery can provide better outcomes. Multidisciplinary approach and surgical pancreatic expertise are essential for successfully treating these patients. However, the lack of consensual definitions and therapies make the results of studies very difficult to interpret and hard to be implemented in some settings. In this article, we review the challenges of borderline resectable pancreatic cancer, the complexity of its management and controversies and point out where further research and international cooperation for a consensus strategy is urgently needed.